2016
DOI: 10.11152/mu.2013.2066.182.ege
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of myometrial infiltration by three-dimensional ultrasonography in patients with endometrial carcinoma: a validation study from Ege University Hospital.

Abstract: Aim: To predict the myometrial invasion with three-dimensional (3D) ultrasonography in a cohort of patients with endometrial carcinoma by a previously described technique. Material and methods: The moyometrial infiltration was evaluated by 3D ultrasonography before surgery in 54 patients with endometrial carcinoma. After scanning the whole uterus by ultrasonography, three perpendicular planes were identified to find the shortest myometrial tumor-free distance to serosa (TDS) by examining the lateral, anterior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…One of the first prospective studies on the use of 3D‐TVS demonstrated that subjective impression of DMI had an overall sensitivity of 92.6% and a specificity of 82.3% 12 . Subsequently, Ergenoglu et al 13 . reported that 3D‐TVS had a sensitivity of 100% and a specificity of 88% for the diagnosis of DMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first prospective studies on the use of 3D‐TVS demonstrated that subjective impression of DMI had an overall sensitivity of 92.6% and a specificity of 82.3% 12 . Subsequently, Ergenoglu et al 13 . reported that 3D‐TVS had a sensitivity of 100% and a specificity of 88% for the diagnosis of DMI.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Ergenoglu et al . 13 reported that 3D‐TVS had a sensitivity of 100% and a specificity of 88% for the diagnosis of DMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that subjective impression of depth invasion had a sensitivity of 92.6%, specificity of 82.3%, negative predictive value of 96.6% and a positive predictive value of 67.7%. Ergenoglu et al reported in 45 patients that subjective impression had a sensitivity of 100%, a specificity of 88%, a positive predictive value of 69% and a negative predictive value of 100% [12].…”
Section: Discussionmentioning
confidence: 99%
“…It provides an evaluation in three different axes and has an advantage to store the image and examine the data later and repeatedly. In a recent study the sensitivity, specificity and negative predictive value of 3D-US for detecting deep myometrial invasion in endometrial cancer patients were 100%, 88% and 100%, respectively [12].…”
Section: Introductionmentioning
confidence: 96%